Development of web-based surveillance system for Internet of Things (IoT) application - Ibrahim, Siti Noorjannah; Hasan Basri, A. H.; Asnawi, Ani Liza (Universitas Ahmad Dahlan in collaboration with IAES Indonesia Section, 2019)
With the advancement of wireless technology, our dependency on smart system has increases to a higher level than before. Without doubt, integration between different technologies becomes inevitable in order create affordable surveillance system. This paper presents the development of with web-based surveillance system with a dedicated Android-based mobile application using a Raspberry Pi and its supporting components i.e., Pi-Camera, PIR motion sensor, Ultrasonic sensor, web-based & mobile application. The designed system also utilizes Node-Red development tools as the platform to integrate all components of the system, MQTT as the communication protocol for data acquisition and ThingSpeak as the middleware. The proposed system can be implemented over the internet using any computer and mobile devices, at anywhere and anytime. The system can automatically stream live video viewed from the Android mobile application and the Raspberry Pi device can send an alert notification to users via email and SMS. The system can be one possible features in smart home system and is considered as an affordable solution, customizable and easy to implement in comparison with other commercial surveillance system products such as CCTV or IP Camera.